Using Paper Texture for Choosing a Suitable Algorithm for Scanned Document Image Binarization - Rafael Dueire Lins; Rodrigo Bernardino; Ricardo da Silva Barboza; Raimundo Correa De Oliveira (Journal of Imaging, 2022)
The intrinsic features of documents, such as paper color, texture, aging, translucency, the kind of printing, typing or handwriting, etc., are important with regard to how to process and enhance their image. Image binarization is the process of producing a monochromatic image having its color version as input. It is a key step in the document processing pipeline. The recent Quality-Time Binarization Competitions for documents have shown that no binarization algorithm is good for any kind of document image. This paper uses a sample of the texture of the scanned historical documents as the main document feature to select which of the 63 widely used algorithms, using five different versions of the input images, totaling 315 document image-binarization schemes, provides a reasonable quality-time trade-off.